การขับเคลื่อนการดำเนินงานตามข้อสั่งการของนายกรัฐมนตรีในห้วงรัฐบาล พลเอก ประยุทธ์ จันทร์โอชา กันยายน 2557 - พฤษภาคม 2564 - ถลัชนันท์ เอ่งฉ้วน (จุฬาลงกรณ์มหาวิทยาลัย, 2021)
This research aims to study characteristics of the Prime Minister’s orders, a process to determine and enforce the Prime Minister’s orders as well as problems and obstacles in operations according to the Prime Minister’s orders in the Government of General Prayut Chan-o-cha from September 2014 - May 2021. A concept of the policy process and implementation was applied. The study was conducted with qualitative research methodology where data were collected from documents and in-depth interviews with 9 related officers. The findings revealed that the orders of Prime Minister General Prayut Chan-o-cha were clearly more than former Prime Ministers, and they were implemented in 4 occasions including the official site visit of the Prime Minister, the National Board Meeting where the Prime Minister Presided over, being a president in opening/closing ceremonies and policy granting and the exercising of the Prime Minister’s orders in case of COVID-19 through the Center for COVID-19 Situation Administration. The orders of the Prime Minister General Prayut Chan-o-cha were emphasized on cross-section integration which was different from previous governments where this kind of operation barely existed and it was used in urgent cases only, and ordered by the operating sector directly. Furthermore, there were some problems regarding definitions and determination of the orders, and responsible entities which were caused by mechanism creation of both regular and ad hoc committees. As a result, in several cases, the Prime Minister did not give an order but an officer who wrote down the Prime Minister’s orders. In term of implementation of the Prime Minister’s Orders, the Prime Minister’s orders related to COVID-19 were exercised with cooperation from relevant sectors at operating level the most, compared with orders in other occasions simultaneously. It was followed by the order of official site visit, and being the president in opening/ closing ceremony and policy granting and the national board meetings, respectively. However, despite operations pursuant to the Prime Minister’s orders, the outcomes as the administration expected were low in overall. Therefore, the researcher has some recommendations that the Prime Minister’s orders should not be considerably given because of negative impacts on other operations of the operating sectors.